2021
DOI: 10.1155/2021/8876991
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Tranexamic Acid in Upper GI Bleeding? A Systematic Review and Meta-Analysis

Abstract: Introduction. Upper gastrointestinal (GI) bleeding is associated with increased morbidity and mortality. Tranexamic acid (TXA) is an antifibrinolytic agent which is licensed in the management of haemorrhage associated with trauma. It has been suggested that tranexamic acid may be able to play a role in upper GI bleeding. However, there is currently no recommendation to support this. Aim. The aim of this study was to synthesise available evidence of the effect of TXA on upper GI bleeding. Methods and Materials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…21 Another systematic review found that tranexamic acid had some beneficial effect in terms of decreasing the risk of re-bleeding and decreasing the need for surgery but there wasn't statistically significant effect on mortality or need of blood transfusion or risk of thromboembolic events. 22 According to the available evidence, tranexamic acid is an effective medication for patients with upper gastrointestinal bleeding and early administration of tranexamic acid may be worth be recommended for the treatment of UGIB in the Emergency Department. 23 In an emergency, it is helpful for clinicians to use risk stratification tools to triage patients who need endoscopy in a suitable time frame and patients who are a low risk that can be followed up on an outpatient basis.…”
Section: Resultsmentioning
confidence: 99%
“…21 Another systematic review found that tranexamic acid had some beneficial effect in terms of decreasing the risk of re-bleeding and decreasing the need for surgery but there wasn't statistically significant effect on mortality or need of blood transfusion or risk of thromboembolic events. 22 According to the available evidence, tranexamic acid is an effective medication for patients with upper gastrointestinal bleeding and early administration of tranexamic acid may be worth be recommended for the treatment of UGIB in the Emergency Department. 23 In an emergency, it is helpful for clinicians to use risk stratification tools to triage patients who need endoscopy in a suitable time frame and patients who are a low risk that can be followed up on an outpatient basis.…”
Section: Resultsmentioning
confidence: 99%
“…Burke et al performed a systemic review of 8 studies that included 12,994 patients with upper gastrointestinal bleeding. Although no effect on mortality was noted, the beneficial effect of TXA on lower rebleeding risk and a decreased need for surgery was observed [ 14 ]. Another systematic review and meta-analysis, including 13 relevant randomized clinical trials and a total of 2271 patients, demonstrated lower mortality and continued bleeding and less need for urgent endoscopic intervention [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the recommendation for early administration of antifibrinolytics is supported by robust data in adult trauma (17,18) and obstetric (32,43) patients, the benefit of antifibrinolytics in adults with gastrointestinal bleeding is less clear. Despite several meta-analyses that have reported a survival benefit, decreased endoscopic intervention, and decreased bleeding (44,45), the recently published Haemorrhage ALleviation with Tranexamic acid -Intestinal system (HALT-IT) trial found no difference in death due to GI bleeding (46). Compared with trauma and obstetric cohorts, the HALT-IT cohort was substantially older; importantly, the effect of age on the hemostatic response to antifibrinolytics has yet to be investigated.…”
Section: Online Clinical Investigationsmentioning
confidence: 99%